A Study on the Use of Specific Points on the Complex Permeability Frequency Curves of Ferrites for Presentation of Magnetic Loss - Jankovskis, J.; Yurshevich, V.; Scavinskis, V. (Elektronika ir Elektrotechnika, 2005)
For polycrystalline ferrites in the frequency range of large amplitude dispersion of complex initial magnetic permeability (known also as domain wall resonance/relaxation region) approximating relations for frequency dependence of magnetic loss tangent are proposed. The distinctive feature of approaches is the use of only several basic parameters of the ferrites: the static magnetic permeability, the saturation magnetization, and, in more general cases, the parameter that is related with grain size distribution scattering. Ill. 3, bibl. 10 (in English; summaries in Lithuanian, English and Russian).